Corpos dissonantes: próteses, performances e imaginário - Bandeira, Ana Paula Neres de Santana (2024)
The movement for more social inclusion has brought in creased visibility to people with disabilities in various everyday contexts. Some disabilities, such as intellectual and sensory impairments, may go unnoticed, while physical disabilities, being more visible, draw attention and challenge cultural norms about the perfect body. The presence of these dissonant bodies using prosthetics or assistive technologies often elicits reactions and questions, highlighting the complexity of perceptions regarding bodily diversity and constructing a whole repertoire that shapes the imagination of both people with and without disabilities. This thesis explores the construction of this imagination through representations of the bodies of individuals with physical disabilities in artistic, sports, and social performances. The research emphasizes technological advancements in prosthetics and assistive technologies, challenging conventional conceptions about the lives of these individuals. Inspired by a music video by artist Viktoria Modesta and a performance at the 2016 Paralympics, the thesis examines how these representations impact the collective imagination. The methodology includes studies of cultural performances, interviews with different groups (individuals with and without disabilities, artists, and athletes with disabilities), and analyses of prosthetized bodies. Cultural performance studies, based on Turner and Schechner, elucidate the construction of imagination in everyday interactions and in artistic and sports events, categorizing ethical, aesthetic, and scientific dimensions interpreted through both the canonical and dissonant perspectives on people with disabilities. Dialogue with Turner reveals the social barriers faced by these individuals, while Schechner's approach highlights the presence of performance in sports and the arts. Through a content analysis of the interviews conducted, the work examines the relationship between bodies and prosthetics, identifying them as elements that influence collective perception and the formation of stigmas and social norms. Le Breton's sociological approach highlights the body as a social, cultural, and symbolic phenomenon. Authors such as Thomson, Goffman, and Malu Fontes contribute to understanding human corporeality and its symbolic representation in society. The conclusion emphasizes the persistence of prejudiced and stigmatizing attitudes, underscoring the importance of active listening to understand the diversity of imaginaries about the body with a disability and promoting inclusive narratives to build a more just and equal society.